Uji Keunikan Sebagai Syarat Diberikan Hak Perlindungan Varietas - Putra, Muh. Aldhyansah Dodhy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research, entitled "Uniqueness Test as a Condition for Plant Variety Rights Protection" aims to find out how a new, distinctness, uniformity, stable concept (DUS) is a requirement for the registration of a plant variety. These four conditions must be met by breeders who will register their plant varieties for protection. The existence of this research is expected to be able to foster understanding for breeders about the laws that regulate in particular Law No. 29 of 2000 concerning the Protection of Plant Varieties and other regulations. The uniqueness test is a test that is discussed in more depth in this study. Juridical normative research uses qualitative methods obtained from literature studies and related laws and regulations. The results obtained from the research include the importance of paying attention to legal rules and individual testing guidelines when conducting DUS technical tests and the importance of paying attention to clear and consistent differences when conducting plant uniqueness tests.